The Implementation of Service Sequence in Improve Operational Service at Muscadet Restaurant, Hotel Sentra Manado - Vesty Like Sambeka; Yurike S. Lewan; Deby Christiani Sendow; Keisya Marode (Jurnal Internasional Riset Bisnis Pariwisata, 2025)
This study aims to analyze problems and find solutions in staff service at Muscadet Restaurant in relation to guest satisfaction at The Sentra Manado Hotel. There are three main issues that are the focus of this study, namely the additional number of participants(guests) in the restaurant, extra service, and overtime. This study applied data through literature study, observation, and interviews. The data obtained was then presented qualitatively. The results of the study found several obstacles in waiter/waitress service. Based on the results of data observation and interviews with guests at The Sentra Manado Hotel, several obstacles in staff service were found. Some of the problems that commonly arise are an additional number of participants, technical problems such as check-in during breakfast, extra services that do not meet expectations, and overtime due to a lack of staff and a lack of cooperation and readiness in serving guests. The conclusion that can be drawn from this study is that the quality of waiter’s service at The Sentra Manado Hotel can meet the needs of guests and make them feel satisfied. Recommendations to improve the quality of restaurant staff service at The Sentra Manado Hotel include conducting training or workshops.